Impact of the 2010 Tsunami on an Endangered Insular Soil-Plant System - Vergara-Egert, P; Soto-Gonzalez, G (2014)
Natural catastrophes could damage island biodiversity and ecosystems, and their effects could become devastating if combined with human disturbances. In this study, we determined the effects of the tsunami occurred in Robinson Crusoe Island (Chile) on 27 February 2010 on an endangered soil-plant system. Using data of endemic Cabbage Trees (Dendroseris litoralis Skottsb.) and soil attributes taken before and after the 2010 event, we developed thematic maps to assess the changes in population size and soil substrate of Cabbage Trees caused by the tsunami. We determined that from 153 pre-tsunami (2009) standing Cabbage Trees, only 66 (43 %) survived in 2011, mostly in elevations above 25 m a.s.l. Before the tsunami, 86 (56 %) of Cabbage Trees were established in humus-rich soil sites whereas after the tsunami, this number declined to 53 (35 %). These results represent the first report of a severe population decline after a tsunami and indicate that tsunamis are an important source of species extinction in small oceanic islands not only by reducing the population size but also by reducing the quality of sites for plant growth. © 2013 Springer Science+Business Media Dordrecht.